SRINTIL: THE INTERSECTION OF TRADITION AND POLITICAL IDEOLOGY THROUGH WOMEN’S EXPLOITATION IN THE DANCER - Haq, Shabrina Fidinil (Serat: Journal of Literary & Cultural Studies, 2025)
ABSTRACT At times, tradition functions not only as a mode to preserve cultural identity and shared values but also as a tool for maintaining political agendas. Using qualitative methods, this study examines the intersection of Tradition and Ideology through the exploitation experienced by Srintil, the main protagonist in the novel The Dancer, written by Ahmad Tohari. The purpose of this study is to investigate how the ronggeng tradition, particularly as performed by Srintil, functions not only as a symbol of cultural identity but also as a site of gender dynamics and a political and ideological instrument in The Dancer. The findings indicate that the novel challenges the romanticized notion of tradition by revealing its connection to power structures, exploitation, and political ideology agendas, often without the awareness or agency of the performer, in this case, Srintil. This article argues that analyzing the main female protagonist's experiences as a ronggeng offers a critical perspective on tradition, particularly those centered around women.